2014
DOI: 10.1007/s11524-014-9900-9
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling Race and Social Context in Understanding Disparities in Chronic Conditions among Men

Abstract: Disparities in men's health research may inaccurately attribute differences in chronic conditions to race rather than the different health risk exposures in which men live. This study sought to determine whether living in the same social environment attenuates race disparities in chronic conditions among men. This study compared survey data collected in 2003 from black and white men with similar incomes living in a racially integrated neighborhood of Baltimore to data from the 2003 National Health Interview Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 27 publications
(42 reference statements)
0
25
0
Order By: Relevance
“…Also, research has reported that a supportive built environment may facilitate one’s ability to achieve recommended levels of physical activity (Giles-Corti & Donovan, 2002; Mozaffarian et al, 2012). However, there is substantial racial segregation that exists in the United States that may affect the built environment of many African American men (Griffith, Schulz, Johnson, & Herbert, 2010; Thorpe et al, 2008; Thorpe et al, 2013c; Thorpe et al, 2015). For instance, compared with White men, African American men are more likely to live in neighborhoods with more constrained access to resources in their built environments that promote physical activity (Marshall et al, 2007; Taylor, Poston, Jones, & Kraft, 2006; Wilson, Kirtland, Ainsworth, & Addy, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Also, research has reported that a supportive built environment may facilitate one’s ability to achieve recommended levels of physical activity (Giles-Corti & Donovan, 2002; Mozaffarian et al, 2012). However, there is substantial racial segregation that exists in the United States that may affect the built environment of many African American men (Griffith, Schulz, Johnson, & Herbert, 2010; Thorpe et al, 2008; Thorpe et al, 2013c; Thorpe et al, 2015). For instance, compared with White men, African American men are more likely to live in neighborhoods with more constrained access to resources in their built environments that promote physical activity (Marshall et al, 2007; Taylor, Poston, Jones, & Kraft, 2006; Wilson, Kirtland, Ainsworth, & Addy, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…49 Following the cumulative burden model of risk suggests that the aggregate effect of institutional or systematic discrimination 50 as exhibited by patterns of racial residential segregation can have the potential to prevent AA men from escaping the deleterious effects of environments that may provide less access to health promoting resources. 11,12,13 Factors such as psychosocial factors, stress, coping strategies, measures of discrimination and personality characteristics were not measured in this study, but are important factors to assess when considering the effects of specific social contexts, as well as events, in the lives of AA men and their contribution to risk for hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…10 These factors are often unaccounted for in the study of AA men's health. -Gilbert et al However, these factors need to be explored to better explain the complexity of AA men's health profile as well determining how this profile is structured by social and physical environments [11][12][13] and policies that negatively shape health outcomes and health behaviors (eg, access and use of health care services), 14,15 especially related to cardiovascular disease. 16 The epidemiological profile of AA men is the result of several intersecting factors 13 that begin to reveal a more complex and concerning story of racialized and gendered experiences for this population.…”
Section: Introductionmentioning
confidence: 99%
“…As such, the social and environmental conditions in which men live must be considered in explaining these important differences in physical activity behaviors ( Wilson-Frederick et al, 2014 ). A growing body of literature has identified associations between the social, environmental, and geographic conditions in which people live and health disparities ( Bleich, Thorpe, Sharif-Harris, Fesahazion, & LaVeist, 2010 ; Fang, Madhavan, Bosworth, & Alderman, 1998 ; Gaskin, Price, Brandon, & LaVeist, 2009 ; Kelley, Bowie, et al, 2016 ; LaVeist et al, 2008 ; LaVeist, Thorpe, Galarraga, Bower, & Gary-Webb, 2009 ; Robert, 1998 ; Roux et al, 2001 ; Thorpe, Bell, et al, 2015 ; Thorpe, Bowie, Wilson-Frederick, Coa, & LaVeist, 2013 ; Thorpe, Kelley, et al, 2015 ; Thorpe, Kennedy-Hendricks, et al, 2015 ). Geographic characteristics are particularly important to examine when interpreting disparities in physical activity, as substantial residential segregation by race/ethnicity exists in the United States, which contributes to variation in access to health-promoting resources such as places to participate in physical activity ( Headen, 2005 ; LaVeist, 2005 ; LaVeist, Gaskin, & Trujillo, 2011 ; Williams & Collins, 2001 ).…”
Section: Introductionmentioning
confidence: 99%